TCP Vegas new techniques for congestion detection and avoidance. - Brakmo, Lawrence S.
Vegas is a new implementation of TCP that achieves between 40 and 70% better throughput, with one-fifth to one-half the losses, as compared to the implementation of TCP in the Reno distribution of BSD Unix. This paper motivates and describes the three key techniques employed by Vegas, and presents the results of a comprehensive experimental performance study?using both simulations and measurements on the Internet?of the Vegas and Reno implementations of TCP.
Keywords: Software; Operating systems; UNIX; Computer systems organization; Computer communication networks; Performance of systems; Measurement of techniques; Design; Experimentation; Measurement; Performance